RANCANG BANGUN KINERJA SDM PENGELOLA KEAMANAN INFORMASI PADA PEMERINTAH DAERAH - Irwansyah Na; Tjiptogoro Dinarjo (Akademika : Jurnal Teknologi Pendidikan, 2016)
This research aims to analyze the factors which influence on Mottled guardian HR performanceinformation security managers, analyze the relationship of those factors to the performance of HUMANRESOURCES, and analyze process architecture HR performance information security manager.Research data consists of primary data obtained directly through survey questionnaires and dataobtained through secondary examination against the literature and documents. The sampling methodis used in stratified random sampling is. From a population of 324 Crypto HR 140 people obtained assamples. This analysis method used in this research is the way the structure equation models (SEM)using Lisrel.The results showed the dominant factor of HUMAN RESOURCES Manager performance ofdeveloped desain of information security is the awareness of information security (Information SecurityAwareness/ISA), competence, perception of support organizations (Perceive OrganizationalSupport/posts), and motivation. As for the relationship of those factors is a good fit of the structuralmodel fit four (4) that the variable information security Awareness (ISA) significantly associated withvariable perceptions of Support Organizations (POS), variable perception of Support Organizations(POS) significantly associated with variable Motivations, variable Competence associated withvariable significant motivation, Motivation is related to significant and variable with variablePerformance.HR Manager-performance of developed desain of information security is done through a processof formation of a culture of security awareness information (ISA) to HR and all officials so thatinformation security is a requirement of the organization. Improved support of institutional setupOrganization through in the management of information security in the provincial government. Improvethe competence of HUMAN RESOURCES so competent in the management of information security ofthe provincial government. With the increase of competence and support organizations will establish aMotivation of HUMAN RESOURCES so as to improve the performance of Crypto Kripto in HRmanagement of information security at provincial governmen